Electric field driven phase transition and possible twining quasi-tetragonal phase in compressively strained BiFeO3 thin films - Lu, Cheng-Liang (2013)
Highly compressively strained BiFeO3 thin films with different thickness are epitaxially grown on (001) LaAlO3 substrates and characterized using various techniques. The quasi-tetragonal phase with a giant axial ratio of ∼ 1.25 and its thickness-dependent evolution are investigated. An interesting twining structure of the quasi-tetragonal phase is evidenced in thicker films through detailed reciprocal space mapping, which becomes more pronounced with increasing film thickness. Moreover, an interesting electric-field driven phase transition was evidenced in the film with a thickness of 38 nm, in which the quasi-tetragonal and rhombohedral phases are close to each other in energy landscape.